Clinical Outcomes and Cost of Ventilator Weaning and Endotracheal Extubation Guided by An Established Ventilator Weaning Protocol in Patients Undergoing Elective Cardiac Surgery - Supanan Innok; Witchuda Dokphueng; Kamol Udol; Worawong Slisatkorn; Prasert Sawasdiwipachai (Siriraj Medical Journal, 2021)
Objective: To compare successful early extubation rates, complications, and cost before and after the use of an established ventilator weaning protocol in patients undergoing elective cardiac surgery. Materials and Methods: Subjects were adult patients undergoing elective cardiac surgery who were clinically stable within 2 hours after surgery. The control group underwent conventional ventilator weaning at the discretion of their attending staff. The intervention group underwent protocol-guided ventilator weaning. The primary outcome was a successful early extubation (within 6 hours after surgery). Secondary outcomes were complications from weaning to 24 hours after surgery, and the relevant cost related to respiratory and cardiovascular care within 24 hours after admission to the postoperative intensive care unit. Results: The primary outcome occurred in 37 out of 65 patients (56.9%) in the intervention group and in 5 out of 65 patients (7.7%) in the control group (adjusted odds ratio 20.6; 95% confidence interval 6.7–62.9, p<0.001). The complication rates were not statistically different between the intervention and control groups (26.2% vs. 20.0%, p=0.41). The relevant cost, approximated by the service charges, related to respiratory and cardiovascular care was significantly less in the intervention group than in the control group (median 2,491 vs. 2,711 Thai baht, p<0.001). Conclusion: The use of the established ventilator weaning protocol after elective cardiac surgery was associated with a higher rate of successful early extubation and lower cost related to respiratory and cardiovascular care compared to the conventional practices of ventilator weaning and extubation. The rates of overall complications were not significantly different.